Exploring the impact of relationship marketing upon customer satisfaction and customer loyalty in Malaysian banking industry - Sung, P. N.; Cheng, Boon Liat * (Inderscience, 2015)
In present extremely competitive and globalize banking context, increasing customer loyalty emerges as one of the most imperative challenges faced by marketers. Cultivating loyal customers is frequently argued to be the single most important driver of organizations’ long-term financial performance, which can lead to increased customer share, lower expenditure, and higher profit. Therefore, marketing academics emphasize the effect of relationship marketing as a strategically vital tool to secure loyal customers. The purpose of this study is to empirically examine the impact of relationship marketing on customer satisfaction and customer loyalty, and to test the impact of customer satisfaction as mediator on the association between relationship marketing and customer loyalty. This study was carried out using the convenience and snowball samplings comprising 162 respondents through the distribution of online structured questionnaires to retail bank customers within the area of Klang Valley, Malaysia. Data analysis was further conducted using the SPSS software, and the results of regression analysis show that relationship marketing is significant in explaining the variation in customer satisfaction and customer loyalty. In addition, customer satisfaction has been proven to partially mediate the relationship marketing-customer loyalty relationship. These findings contribute to the understanding on the relationship between relationship marketing, customer satisfaction, and customer loyalty which provide critical implications for retail bank managers and highlight possible directions for future research.